A Critical Appraisal of the Economics Rationale of Government-Subsidized Manpower Training - Mehmet, Ozay (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1970)
The author endeavors to present a detailed analysis of the economic rationale of a manpower training policy, and provides useful insights on its limits through a selective study of macro-, micro-, and welfare economic theory.